TINJAUAN YURIDIS TERKAIT KEJAHATAN PENCURIAN PADA MALAM HARI DI MINIMARKET 24 JAM - Elfrida Ratnawati Gultom; Diky Nur Rahmandani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Theft is the most common crime in society and is an activity that is one of the things that people fear. This is because the process of theft often threatens or injures someone. In terms of this research discusses the juridical review of crime at night in the 24 hour mini market. Theft in this discussion is divided based on two times, namely during the day and at night. Regulations regarding the crime of theft at night are regulated according to Article 363 of the Criminal Code, there is a ballast element related to the crime of theft which is carried out at night based on the lack of lighting and the time used is the time that is usually used by someone to rest. The method used in this study uses a normative method which examines the legal point of view from a factual perspective. As well as a literature study by collecting reading materials, data, and laws and regulations. The purpose of this study is to be able to identify the rules that occur when a theft process occurs at night at a 24-hour minimarket.Keywords: Theft; Evening; Mini Market